Queer history in Cymbeline. (2nd July 2016) - Miller-Tomlinson, Tracey
Abstract : This essay considers Cymbeline 's inquiry into the dynamics of history and desire alongside work in queer studies that attends to the indeterminacy of desire both in and for history. It argues that Cymbeline draws on Ovidian approaches to history, eroticism and narrative to model a multi-vocal historiography that foregrounds non-heteronormative experiences of desire.